2006
DOI: 10.1111/j.1368-5031.2006.00786.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous lispro and intravenous regular insulin treatments are equally effective and safe for the treatment of mild and moderate diabetic ketoacidosis in adult patients

Abstract: In this prospective, randomised, open trial, we wanted to evaluate the efficacy and safety of hourly subcutaneous (SC) insulin lispro administration in the treatment of diabetic ketoacidosis (DKA) in comparison with intravenous (IV) regular insulin treatment. Twenty patients were enrolled in the study. The patients were randomly assigned into two groups. Following a bolus injection of 0.15 U/kg IV regular insulin, group L received half of this dose as hourly SC insulin lispro while group R was treated conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 16 publications
1
48
0
2
Order By: Relevance
“…Studies comparing treatment of DKA using subcutaneous or intramuscular insulin against conventional IV insulin infusions found slower plasma glucose reductions at 1 h (failure to reduce by 10%) (55) and at 3 h (56) and slower ketone clearance (56). …”
Section: Resultsmentioning
confidence: 99%
“…Studies comparing treatment of DKA using subcutaneous or intramuscular insulin against conventional IV insulin infusions found slower plasma glucose reductions at 1 h (failure to reduce by 10%) (55) and at 3 h (56) and slower ketone clearance (56). …”
Section: Resultsmentioning
confidence: 99%
“…The study found no statistically significant difference in the length of hospital stay, duration of treatment, or amount of insulin received among the study groups. These findings were supported by another article with a smaller sample size 3 , and a 2016 Cochrane Review 4 of this topic concluded that, on the basis of low quality evidence, treatment of DKA with subcutaneous insulin was neither superior nor inferior to IV insulin.…”
Section: Marlene Aziza Azar Is a Fourth Year Medical Student Atsupporting
confidence: 65%
“…76 Potential candidate patients include those who are alert and do not otherwise need admission to a critical care area, have a pH above 7.0, and bicarbonate of at least 10 mmol/L (≥10 mEq/L) 77. Four prospective randomized studies in adult patients with diabetic ketoacidosis compared subcutaneous rapid acting insulin (initial bolus of 0.3 units/kg followed by 0.1-0.2 units/kg every 1-2 hours) with conventional diabetic ketoacidosis treatment and found no difference in patient outcomes 77787980. With subcutaneous insulin regimens, administration of intravenous fluids and electrolytes, as well as monitoring, is identical to what is recommended with intravenous insulin therapy.…”
Section: Acute Managementmentioning
confidence: 99%